The Effect of Relational Capability on Learning Capability: A Study on SMEs in Klaten, Central Java, Indonesia - Utomo, Humam Santosa; Wibawa, Tri; Widjanarko, Hendro; Suratna, Suratna (RSF Conference Series: Business, Management and Social Sciences, 2021)
Learning capability is an important aspect in sustaining a business, especially in a rapidly changing environment. SMEs in Klaten, Central Java, collaborate in an association to solve the same problem. The purpose of this research is to test and analyze the effect of relational ability on learning ability.The study was conducted on 100 food SMEs in Klaten, Central Java using a quantitative approach. The research instrument was a questionnaire to obtain data. The analytical tool used is WarpPLS. The research findings show that relational capability has a significant effect on learning capability.